Secondary metabolites in four cultivars of Plumeria sp. Relationships with the organ and the environment (Bioagro, 2024)
Secondary metabolites (SM) are molecules synthesized in low concentrations by plants, playing an important role in their adaptation to the environment, which depends on internal and external conditions. In Apocynaceae, Plumeria sp. is a plant cultivated as an ornamental, constituting a source of biologically active compounds, some of which are used as drugs. A phytochemical analysis was performed using thin layer chromatography on ethanolic extracts obtained from aerial and underground organs of P. pudica 'Biotipo V', P. pudica 'Bridal White', P. obtusa 'Singapure White' and the hybrid P. rubra x P. obtusa 'Mele Pa Bowman', collected in rainy, transition and drought seasons, from plants grown in the Agronomy School, Universidad Centroccidental Lisandro Alvarado, in Venezuela. The highest concentration of alkaloids for all materials was determined, in the stem, in drought and also in transition, for P. pudica and P. obtusa. Similarly, phenols were more abundant, in roots, and in drought. In the case of flavonoids, the highest concentration values were obtained at the stem in drought, for almost all materials, except for the hybrid, in which it occurred in the leaves at the same time and in the inflorescences, in transition. Saponins were determined, in all cultivars, at very low concentrations. The time of collection was an important factor in the synthesis of the SM and concentration of these, the differences could be related to stressors, which influence bioproduction.
Keywords: alkaloids; flavonoids; phenols; saponins